Chapter Three. Conservation agriculture for regenerating soil health and climate change mitigation in smallholder systems of South Asia - Jat, Mangi L.; Gathala, Mahesh Kuma; Choudhary, Madhu; Sandeep Sharma; Jat, H.S.; Singh, Yadvinder P. (Academic Press, 2023)
The increase in agriculture production to meet the food demand of growing human population from a limited availability of arable land with low environmental footprints and preserving natural resources (soil, water and air) simultaneously are major challenges in South Asia. The situation is further complicated by the climate change, which will further lower the food production, compounding the challenge of meeting food demand. Conservation Agriculture (CA) is solution to several challenges being faced in farming such as soil health, climate change, water scarcity, agricultural pollution, farm profitability, human health, etc. This exhaustive review examines the published literature from South Asia to assess the impact of CA on soil organic carbon (SOC) and the subsequent impacts on soil health (physical, chemical and biological properties), C sequestration and greenhouse gases emissions in major cropping systems. The results from several studies demonstrated that CA increased SOC and improved soil health parameters, mainly in the surface soil layer. The effects of CA on the changes in soil pH and electrical conductivity are small. The CA showed a remarkable positive impact on the nutrient availability in the soil. The CA system helped in both climate change mitigation and adaptation for sustainable crop production. The present gaps in our knowledge in soil health assessment and research agenda to fill the gaps are also included in this chapter. We hope this review of past accomplishments, current activities, and future opportunities will stimulate additional soil health research throughout the 21st century.